1989
DOI: 10.1145/67450.67523
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical formula editor for CAI

Abstract: Many students in lower grades who study mathematics with computers have difficulty in inputting formulas by using existing methods. It would be much easier for them if they could input formulas naturally, as they appear in textbooks. This paper describes such an interface program module for use in CAI. This module makes it easy for students to input and edit complex formulas solely by key operations, without using a mouse. The difference between the module and existing mathematical expression editors is that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Nakayama (1989). MFE is designed as a set of procedures to be incorporated into other programs (in particular, those aimed at computer aided instruction), and called by them for two-dimensional input and output.…”
Section: Document Processing Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakayama (1989). MFE is designed as a set of procedures to be incorporated into other programs (in particular, those aimed at computer aided instruction), and called by them for two-dimensional input and output.…”
Section: Document Processing Systemsmentioning
confidence: 99%
“…An experiment by Nakayama with 17 and 18 year-old high school girls showed that even complex formulas could be entered with only 30 minutes of training . (Nakayama, 1989).…”
Section: Document Processing Systemsmentioning
confidence: 99%
“…Typing an ASCII form of the mathematical expression, or Issuing a sequence of commands to a structure-based math editor. Currently, most people who need to enter mathematical expressions use manual conversion (typing an ASCII form of the expression, or issuing editor commands to enter the structure of the expression [1]). In contrast, the technology for output of mathematical notation is mature and widely available (bottom part of the figure).…”
Section: Notation Generatormentioning
confidence: 99%
“…The ability for users to interactively create and manipulate mathematical expressions is very important for systems such as Science Communication Environment, Computer Algebra Systems, and Webbased Mathematics Education [8,14,15,25,26]. MathEdit is a browser-based mathematical expression editor developed jointly by Lanzhou university/China and Kent University/USA [2,23,27].…”
Section: Introductionmentioning
confidence: 99%